Phylogenetic relationships within western African Torrent Toads (Anura: Bufonidae: Werneria) with focus on the taxonomic status of Werneria preussi and Atelopus africanus - Petzold, Alice; Norden, Vanessa; Gonwouo, Nono L.; Segniagbeto, Gabriel H.; Ohler, Annemarie; Rödel, Mark-Oliver (Zootaxa, 2025)
Bufo preussi Matschie, 1893 from Mt. Cameroon was the first African Torrent toad to be described, soon followed by Atelopus africanus Werner, 1898 from Bismarkburg in Togo. Shortly after, both species were considered conspecific and, currently, both fall under the name Werneria preussi following taxonomic revisions. The type locality of A. africanus was consequently believed to be an error, especially due to the absence of reports of Werneria individuals in Togo in subsequent years. However, it remained uncertain if this synonymy is justified or if A. africanus may indeed represent a valid but potentially extinct species. To answer this question, we generated the first mitochondrial data (12S, 16S and COI) for name-bearing types of W. preussi and A. africanus using a museomic approach. This was further complemented by mitochondrial and nuclear data of contemporary relatives. Our multi-gene phylogeny inferred from mitochondrial data showed that W. preussi and A. africanus constitute a well-supported monophyletic group, which further includes W. submontana. Together with distance values falling below the commonly used species threshold of 3% for 16S and 6% for COI, this result provides strong evidence for A. africanus being a junior synonym of W. preussi, and the absence of this genus in Togo. It further indicates that W. submontana does not represent a species distinct from W. preussi, but rather a geographic variety differing morphologically from topotypic W. preussi. Due to this morphological differentiation, we propose to consider the W. submontana populations as a distinct subspecies and herein introduce the new name Werneria preussi submontana comb. nov. We further designate a lectotype for W. preussi, in order to increase nomenclatural stability and facilitate future research focusing on African Torrent Toads.